Habitual side-specific loading leads to structural, mechanical, and compositional changes in the patellar tendon of young and senior lifelong male athletes - Jessen, S.; Eibye, K.; Christensen, P. M.; Hostrup, M.; Bangsbo, J. (Journal of Applied Physiology, 2021)
Effects of lifelong physical activity on tendon function have been investigated in cross-sectional studies, but these are at risk of "survivorship" bias. Here, we investigate whether lifelong side-specific loading is associated with greater cross-sectional area (CSA), mechanical properties, cell density (DNA content), and collagen cross-link composition of the male human patellar tendon (PT), in vivo. Nine seniors and six young male lifelong elite badminton players and fencers were included. CSA of the PT obtained by 3-tesla MRI and ultrasonography-based bilateral PT mechanics were assessed. Collagen fibril characteristics, enzymatic cross links, nonenzymatic glycation (autofluorescence), collagen, and DNA content were measured biochemically in PT biopsies. The elite athletes had a =15% side-to-side difference in maximal knee extensor strength, reflecting chronic unilateral sport-specific loading patterns. The PT CSA was greater on the lead extremity compared with the nonlead extremity (17%, P = 0.0001). Furthermore, greater tendon stiffness (18%, P = 0.0404) together with lower tendon stress (22%, P = 0.0005) and tendon strain (18%, P = 0.0433) were observed on the lead extremity. No effects were demonstrated from side-to-side for glycation, enzymatic cross link, collagen, and DNA content (50%, P = 0.1160). Moreover, tendon fibril density was 87 ± 28 fibrils/µm2 on the lead extremity and 68 ± 26 fibrils/µm2 on the nonlead extremity (28%, P = 0.0544). Tendon fibril diameter was 86 ± 14 nm on the lead extremity and 94 ± 14 nm on the nonlead extremity (-9%, P = 0.1076). These novel data suggest that lifelong side-specific loading in males yields greater patellar tendon size and stiffness possibly with concomitant greater fibril density but without changes of collagen cross-link composition.